Web Radio: educational nursing care technology addressing cyberbullying students' statements - Leidy Dayane Paiva de Abreu; Raimundo Augusto Martins Torres; Karlla da Conceição Bezerra Brito Veras; Aretha Feitosa de Araújo; Isabela Gonçalves Costa; Gislanny Rodrigues Oliveira
ABSTRACT Objectives: to understand, from the vocabulary universe of young students, the knowledge and statements on cyberbullying via Web Radio Associação de Jovens de Irajá. Methods: a qualitative research. Students' speech questions were used on the web radio's message board and on the station's social networks; 35 students participated. The analysis was based on Paulo Freire's Culture Circle and Thematic Analysis. Results: the following categories emerged: "Cyberbullying: Reading the World Youth School", which describes the vocabulary universe of youths: social networks, bullying, internet, cyberbullying, violence, fakes and anonymity; and "Is Cyberbullying a Joke or Virtual Violence?", which points to the health consequences, therapeutic alternatives of treatment and punitive laws. Final Considerations: nursing educational care with schoolchildren via web radio brought contributions on cyberbullying, since the youths adopted reflective postures in the face of the problem.